Side Effects of Bacillus Calmette-Guerin (BCG) in the Treatment of Intermediate- and High-risk Ta, T1 Papillary Carcinoma of the Bladder: Results of the EORTC Genito-Urinary Cancers Group Randomised Phase 3 Study Comparing One-third Dose with Full Dose and 1 Year with 3 Years of Maintenance BCG - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
Background: Although bacillus Calmette-Guerin (BCG) has proven highly effective in non-muscle-invasive bladder cancer (NMIBC), but it can cause severe local and systemic side effects. Objectives: The objective was to determine whether reducing the dose or duration of BCG was associated with fewer side effects. Efficacy comparisons of one-third dose versus full dose BCG given for 1 yr versus 3 yr have previously been published. Design, setting, and participants: After transurethral resection, patients with intermediate-and high-risk NMIBC without carcinoma in situ were randomised to one-third dose or full dose BCG and 1 yr or 3 yr of maintenance. Outcome measurements and statistical analysis: Local and systemic side effects were recorded at every instillation and divided into three time periods: during induction, during the first year after induction, and during the second and third years of maintenance. Results and limitations: Of the 1316 patients who started BCG, 826 (62.8%) reported local side effects, 403 (30.6%) reported systemic side effects, and 914 (69.5%) reported local or systemic side effects. The percentage of patients with at least one side effect was similar in the four treatment arms (p = 0.41), both overall and in the different time periods. The most frequent local and systemic side effects were chemical cystitis in 460 (35.0%) patients and general malaise in 204 patients (15.5%); 103 patients (7.8%) stopped treatment because of side effects. No significant difference was seen between treatment groups (p = 0.74). In the 653 patients randomised to 3 yr of BCG, 35 (5.4%) stopped during the first year, and 21 (3.2%) stopped in the second or third year. Conclusions: No significant differences in side effects were detected according to dose or duration of BCG treatment in the four arms. Side effects requiring stoppage of treatment were seen more frequently in the first year, so not all patients are able to receive the 1-3 yr of treatment recommended in current guidelines. (C) 2013 European Association of Urology. Published by Elsevier B. V. All rights reserved.
Keywords: Urothelial carcinoma; Non-muscle-invasive bladder cancer; Maintenance BCG; Dose reduction; Side effects; MITOMYCIN-C; EUROPEAN ORGANIZATION; PRACTICE RECOMMENDATIONS; UROTHELIAL CARCINOMA; FORMAL METAANALYSIS; III TRIAL; 27 MG; PROGRESSION; TOXICITY; TUMORS